Impact of Body Composition in Overweight and Obese Patients With Localised Renal Cell Carcinoma - DARBAS, TIFFANY; FORESTIER, GERAUD; LEOBON, SOPHIE; PESTRE, JULIA; JESUS, PIERRE; LACHATRE, DENIS; TUBIANA-MATHIEU, NICOLE; DESCAZEAUD, AURELIEN; DELUCHE, ELISE (In vivo (Athens), 2020)
Background/Aim: To investigate the impact of body composition on morbidity and mortality at the initial diagnosis of localised renal cell carcinoma (RCC) in patients with overweight or obesity. Patients and Methods: Sarcopenia was defined using sex-specific cut-off points and other body composition parameters by median values with computed tomography imaging. Results: Among the 96 patients, 40 had sarcopenia (43.0%) at diagnosis. Body composition had no effect on morbidity and 5-year disease-free survival contrary to the classic factors (p<0.05). In the subgroup of obese patients, those with sarcopenia had a poor prognosis (p=0.04) but not in the population with overweight (p=0.9). Conclusion: Sarcopenia was frequently associated with localised RCC at the initial diagnosis. Body composition did not affect morbidity or outcomes. BMI was involved in morbidity and there was paradoxically longer survival in the obesity group.